The effect of KAATSU style exercises on some anthropometric variables of the upper extremities of bodybuilders - Hassan, AliZuheer (International Journal of Psychosocial Rehabilitation, 2020)
The study investigates the role and effect of kaatsu-style resistance exercises for some amateur bodybuilders, as well as the effectiveness of these exercises and the method for hypertrophy of the biceps muscle in the upper extremities of the arm. As for the problem that the researcher noticed, the use of loads of weightlifting exercises continuously and with high intensity and large repetitions can cause injury to the body of the athlete as a result of these exercises or through the association of these exercises with drugs such as steroids or random nutritional supplements used to enhance the effectiveness of training. Avoiding this phenomenon and using the correct relationship between work and rest usually achieves a full recovery. The experimental method was also used for its suitability and the nature of the research, as the research community was chosen by a random method, which numbered (16) athletes, and after analyzing and discussing the results, the researcher concluded that the use of this method according to the kaatsu exercises effectively contributed to amplifying the biceps muscle of amateur bodybuilding athletes.